2015
DOI: 10.1016/j.jpowsour.2014.09.184
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electrochemical refrigeration power plant using natural gas with ∼100% CO2 capture

Abstract: We propose an efficient Natural Gas (NG) based Solid Oxide Fuel Cell (SOFC) power plant equipped with ~ 100 % CO 2 capture. The power plant uses a unique refrigeration based process to capture and liquefy CO 2 from the SOFC exhaust. The capture of CO 2 is carried out via condensation and purification using two rectifying columns operating at different pressures. The uncondensed gas mixture, comprising of relatively high purity unconverted fuel, is recycled to the SOFC and found to boost the power generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Under the conditions of removing 100% CO 2 by the fuel regenerator, a net AC efficiency of over 69% (LHV) and CO 2 capturing rate of over 98% are possible. The net AC efficiency of a natural gas-fueled power plant with 100% CO 2 capture by a refrigeration process was reported as 70.4%-76.0% (LHV) (12). Although our system design and parameters were different from those in the reported study, similar results were obtained using the fuel regenerator with CO 2 removal.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Under the conditions of removing 100% CO 2 by the fuel regenerator, a net AC efficiency of over 69% (LHV) and CO 2 capturing rate of over 98% are possible. The net AC efficiency of a natural gas-fueled power plant with 100% CO 2 capture by a refrigeration process was reported as 70.4%-76.0% (LHV) (12). Although our system design and parameters were different from those in the reported study, similar results were obtained using the fuel regenerator with CO 2 removal.…”
Section: Resultssupporting
confidence: 64%
“…They experimentally reported stable power generation with a net AC efficiency estimated to 69.0% (LHV) with thermal self-sustainability (11). E. I. Al-Musleh et al showed the possibility of generating power with a net AC efficiency of over 70% (LHV) by capturing 100% CO 2 using the cold heat of liquefied natural gas (12). As described above, some studies examined an anode off-gas recycling SOFC system with a fuel regenerator including CO 2 removal and obtained the fuel utilization rate and/or the power generation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Al-musleh et al [190] proposed a process design of a solid oxide fuel cell power plant based on natural gas and CO 2 capture and liquefaction, referred to as an electrochemical refrigeration power plant. This process could achieve about 100% CO 2 capture and liquefaction, and the power generation efficiency was 70.4-76%.…”
Section: Lng Cold Energy Utilizationmentioning
confidence: 99%
“…Natural gas (NG) is considered the best fuel for this transition from nonrenewables to renewables. Compared to oil and coal, it has a higher heating value (kJ/kg), lower cost ($/kJ), lower CO 2 emissions, and negligible gaseous (CO, NOx, SOx) and particulate emissions . About 80% of the proven NG reserves are located in only 10 countries, hence it is of paramount importance that the transport of NG over long distances is both economical and efficient .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to oil and coal, it has a higher heating value (kJ/kg), lower cost ($/kJ), lower CO 2 emissions, and negligible gaseous (CO, NOx, SOx) and particulate emissions. 1 About 80% of the proven NG reserves are located in only 10 countries, hence it is of paramount importance that the transport of NG over long distances is both economical and efficient. 2 Therefore, NG is normally transported in liquid form (LNG or Liquefied NG) at 113 K, which reduces its volume by a factor of 600 at ambient pressure.…”
Section: ■ Introductionmentioning
confidence: 99%